Evidence supporting laparoscopic hernia repair in children. Issue 3 (June 2018) - Jessula, Samuel; Davies, Dafydd A.
Abstract : Purpose of review: Pediatric inguinal hernias are a commonly performed surgical procedure. Currently, they can be approached via open or laparoscopic surgery. We summarize the current evidence for laparoscopic inguinal hernia repairs in children. Recent findings: Laparoscopic and open inguinal hernia repair in children are associated with similar operative times for unilateral hernia, as well as similar cosmesis, complication rates and recurrence rates. Bilateral hernia repair has been shown to be faster through a laparoscopic approach. The laparoscopic approach is associated with decreased pain scores and earlier recovery, although only in the initial postoperative period. Laparoscopy allows for easy evaluation of the patency of contralateral processus vaginalis, although the clinical significance of and need for repair of an identified defect is unclear. Summary: Laparoscopic surgery for pediatric inguinal hernias offers some advantages over open repair with most outcomes being equal. It should be considered a safe alternative to open repair to children and their caregivers.